1996
DOI: 10.1142/s0217751x96000092
|View full text |Cite
|
Sign up to set email alerts
|

CALCULATION OF GROMOV-WITTEN INVARIANTS FOR CP3, CP4AND Gr(2, 4)

Abstract: Using the associativity relations of the topological Sigma Models with target spaces, CP 3 , CP 4 and Gr(2, 4) , we derive recursion relations of their correlation and evaluate them up to certain order in the expansion over the instantons. The expansion coeffieients are regarded as the number of rational curves in CP 3 , CP 4 and Gr(2, 4) which intersect various types of submanifolds corresponding to the choice of BRST invariant operators in the correlation functions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…We first discuss the Virasoro generators in the case of CP N manifolds and show that the Virasoro conditions eq. (1) correctly reproduce the results on instanton numbers of projective spaces obtained by [2,3,4,5,13] using the associativity of quantum cohomology ring. We then present the general form of the Virasoro operators for a wider class of Fano varieties.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…We first discuss the Virasoro generators in the case of CP N manifolds and show that the Virasoro conditions eq. (1) correctly reproduce the results on instanton numbers of projective spaces obtained by [2,3,4,5,13] using the associativity of quantum cohomology ring. We then present the general form of the Virasoro operators for a wider class of Fano varieties.…”
supporting
confidence: 82%
“…We have tested the operators (47) in the case of Grassmannian manifold Gr(2, 4) for which genus-0 instanton data exist [5]. We found that Virasoro conditions in fact reproduce correct instanton numbers of Gr (2,4).…”
mentioning
confidence: 99%
“…In such cases, identities ∂ t l κ m = ∂ t m κ l are satisfied automatically and integrable conditions are turned into formulae These determine instanton parts of prepotentials completely [12,13,14]. Under these conditions (4.…”
Section: Fusion Relations For Operatorsmentioning
confidence: 99%
“…Also it is known that the closed string amplitudes {κ m } can be calculated recursively [12,13,14] by associativity relations of operators for Fano manifolds. In our case these associativities appear naturally as integrable conditions for a set of differential equations satisfied by the …”
Section: Introductionmentioning
confidence: 99%
“…[6,7,8,9,10]. This method is efficient and general, however, is limited to the genus g = 0 case at the moment.…”
Section: When the Target Space M Is A Calabi-yau Manifold A Special mentioning
confidence: 99%